HUBUNGAN KAUSALITAS ANTARA TINGKAT BUNGA, TINGKAT INFLASI DAN KURS DI INDONESIA TAHUN 2010 - 2019 - Ririn, Indria; Antony, Mayes; Rahmat, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the causal relationship between the interest rate, the inflation rate and the exchange rate in Indonesia. This study uses secondary data obtained from the official website of Bank Indonesia, namely Indonesian Financial Economics Statistics (SEKI). The analytical method used is the Grenger causality analysis. In conducting the Grenger causality test using the help of the Eviews program, the data used in this study is the time series data per month in 2010 – 2019. Based on the results of the study, the results of the Granger causality test were obtained, during the observation period which included time vulnerability per month 2010 - 2019 showing that interest rates and inflation rates in Indonesia have a unidirectional causal relationship, namely interest rates that affect inflation, which means changes in interest rates can affect changes inflation. Interest rates and exchange rates in Indonesia have a unidirectional causality, namely the unidirectional influence of interest rates can affect exchange rate conditions, which means that interest rate movements can affect exchange rate conditions in Indonesia. However, there was no effect of exchange rate on interest rates. There is no causality relationship between the inflation rate and the exchange rate in Indonesia. Which means that there is no reciprocal relationship between the inflation rate and the exchange rate.Keywords: Bank Indonesia Interest Rates, Inflation, Exchange Rates, Grenger Causality